2019
DOI: 10.3390/app9235101
|View full text |Cite
|
Sign up to set email alerts
|

A Connected and Autonomous Vehicle Reference Architecture for Attack Surface Analysis

Abstract: Connected autonomous vehicles (CAVs) will be deployed over the next decade with autonomous functionalities supported by new sensing and communication capabilities. Such functionality exposes CAVs to new attacks that current vehicles will not face. To ensure the safety and security of CAVs, it is important to be able to identify the ways in which the system could be attacked and to build defences against these attacks. One possible approach is to use reference architectures to perform an attack surface analysis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
35
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
3
2

Relationship

1
9

Authors

Journals

citations
Cited by 46 publications
(35 citation statements)
references
References 45 publications
(53 reference statements)
0
35
0
Order By: Relevance
“…They concluded that 3D point cloud classifiers, such as PointNet [44] or PointNet++ [45] are weak to adversaries leading to a high attack success rate. Another possible target could also be the algorithms utilized for the processing of the data (e.g., repair mechanic installing hacking device [46]). To analyze all possible scenarios, we can divide the threat models into two categories.…”
Section: A Adversarial Threat Modelmentioning
confidence: 99%
“…They concluded that 3D point cloud classifiers, such as PointNet [44] or PointNet++ [45] are weak to adversaries leading to a high attack success rate. Another possible target could also be the algorithms utilized for the processing of the data (e.g., repair mechanic installing hacking device [46]). To analyze all possible scenarios, we can divide the threat models into two categories.…”
Section: A Adversarial Threat Modelmentioning
confidence: 99%
“…A very productive approach to threats analysis is to consider the system as a whole, identify possible parts of it and then discover security problems that might be associated with each part of the system. This is done, for example, in the paper [ 9 ], exploring the vulnerabilities of connected and autonomous vehicles (CAV) and proposing a reference CAV architecture tailored for attack surface analysis.…”
Section: Related Workmentioning
confidence: 99%
“…At the same time, Figure 1 refers to the sections of our work which apply the respective analysis. With a general focus on the IoV location service application (see Section III-A), we leverage sub-architectures, defined in the work [10], to model IoV system assets. This measure reduces the complexity and facilitates our security analysis.…”
Section: Introductionmentioning
confidence: 99%